Práticas de letramento em uma comunidade de assentamento de reforma agrária: uma investigação a partir de relatos de estudantes do campo - Cordeiro, Claudia Talochinski (2021)
This study is part of the Postgraduate Program in Language Studies (PPGEL) of the Federal Technological University of Paraná (UTFPR), in the area of concentration of Language and Technology and in the research line of Multiliteracies, discourses and the production process of sense. In the field of studies on the uses of reading and writing, the term ‘literacy’ has been often confused with literacy and much has been said and studied about the subject. Due to the understanding of the theme, there is a range of terms related to literacy such as: digital literacy, multiliteracies, literacy agency, literacy practices and events, among others. Therefore, initially, we seek to define and study the nomenclatures referred to literacies, in order to achieve the main objective of this research, which is to analyze the practices of literacy reconstructed in the reports of students from a Contested Agrarian Reform Settlement school, in the municipality of Lapa-PR. From a theoretical point of view, the research is based on new literacy studies, based on the writings of COPE and KALANTZIS (2000; 2005; 2008; 2013), Street (1988; 2014; 2020), Kleiman (1992; 1995; 2007), among others, which are part of the field of language studies, more specifically in the field of Applied Linguistics. The methodology used met the requirements of a qualitative-interpretative research, with a participating teacher, having as methodological tools for data collection two online meetings (meets) with the participants, a questionnaire and written production of the personal report genre. From the data, it was possible to perceive some literacy practices and events reconstructed in the participants’ texts.